The Role of Women’s Language in Transwoman’s Identity in The Documentary Disclosure (2021) - Nadhifa, Aqilah Aulia; Suyatman, Ujang; Ruminda (General English Education, 2025)
This research explores the use of women’s language by trans women in the documentary Disclosure. The research is based on Robin Lakoff and Judy Pearson’s theory, which explains the various language features often used by women to express themselves in social contexts and also how the function of women’s language. These features include women’s language, which reflects the way women communicate. This study aims to identify the types of women’s language features used by transwomen in the documentary and understand the function of the language in constructing, expressing, and representing their gender identity.  The method used in this research is qualitative, with data collection techniques in the form of observation and analysis of dialog contained in the documentary. The dialogues spoken by Transwoman are classified based on Lakoff's women’s Language and Pearson’s Function of Women’s Language theory, then analyzed to see how language choices play a role in representing their gender identity. The results of this study are expected to reveal the relationship between the language features used and the process of gender identity construction in the media. In addition, this research makes a significant contribution to the study of sociolinguistics by expanding the understanding of the relationship between language, gender, and also identity.